Large-size grain-boundary-free CsPbCl 3(1–x) Br 3x Single crystal thin film and its preparation and application
During the preparation of CsPbCl3(1–x)Br3x material, preheating the Cs and Pb sources and combining multi-stage temperature control methods, a large-size, grain-free single-crystal film was successfully prepared, solving the limitations in material size and performance in the prior art, and realizing the possibility of a high-performance tunable laser.
Patent Information
- Application Number
- CN202211267644.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-17
AI Technical Summary
The prior art lacks large-size, grain-free CsPbCl3(1–x)Br3x single-crystal thin film materials, and it is difficult to form high-performance tunable lasers.
By pre-heating the Cs source and the Pb source at T1 temperature and combining the combined control of T2 and T3 temperatures under negative pressure, a large-size grain-free CsPbCl3(1–x)Br3x single crystal thin film was successfully prepared.
The preparation of large-size grain-free CsPbCl3(1–x)Br3x single crystal thin film has been realized, with excellent tunability and optical gain performance, and is suitable for the preparation of high-performance tunable lasers.
Smart Images

Figure CN115679446B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of laser materials, and specifically relates to a CsPbCl 3(1–x) Br 3x Single crystal thin film. Technical Background
[0002] CsPbX3 (X is Cl, Br or I) materials have broad application prospects in light-emitting diodes (LEDs), photodetectors and lasers due to their excellent optoelectronic properties, such as high optical absorption coefficient, tunable band gap and high luminescence quantum efficiency. [1-3] In addition, CsPbX3 material also has excellent stability and can show excellent photoelectric properties even when exposed to air. [4-5] .
[0003] It is well known that the applications of CsPbX3 (X = Cl / Br / I) materials are closely related to their band gaps, and band gap engineering of CsPbX3 materials has been demonstrated to be a viable strategy to achieve desired optical and electrical properties. [6-7] . CsPbX3 materials with tunable band gap can be used in wavelength tunable lasers. Wavelength tunable lasers are lasers that can continuously change the laser output wavelength within a certain range. This type of laser can be widely used in many fields such as spectral analysis, communications, biomedicine, etc. [8-9] .
[0004] There is a great correlation between the physical phase, structure and performance of CsPbX3 (X = Cl / Br / I). However, in the prior art, CsPbX3 is mainly prepared by solution crystallization methods such as inverse temperature crystallization, antisolvent vapor assisted crystallization and cooling saturated crystallization, and the material mainly presents nanowires, nanosheets and amorphous film structure characteristics, and the optoelectronic application scenarios of this type of material are relatively limited. The industry is still lacking large-size single crystal thin film materials of CsPbX3 composite phase.
[0005] [1]Lim J, MT,Sakai N,et al.Elucidating the long-range chargecarrier mobility in metal halide perovskite thin films[J].EnergyEnvironmental Science,2019,12(1):169-176.
[0006] [2]Saidaminov MI,Abdelhady AL,Murali B,et al.High-quality bulk hybridperovskite single crystals within minutes by inverse temperaturecrystallization[J].Nature communications,2015,6(1):1-6.
[0007] [3]Park N-G.Perovskite solar cells:an emerging photovoltaictechnology[J].Mater Today,2015,18(2):65-72.
[0008] [4]Jiang G,Guhrenz C,Kirch A,et al.Highly Luminescent and Water-Resistant CsPbBr3-CsPb2Br5 Perovskite Nanocrystals Coordinated with PartiallyHydrolyzed Poly(methyl methacrylate)and Polyethylenimine[J].ACS Nano,2019,13(9):10386-10396.
[0009] [5]You J,Meng L,Song T-B,et al.Improved air stability of perovskitesolar cells via solution-processed metal oxide transport layers[J].Naturenanotechnology,2016,11(1):75-81.
[0010] [6]Guo J,Fu Y,Lu M,et al.Cd-Rich Alloyed CsPb 1-x Cd xBr3 PerovskiteNanorods with Tunable Blue Emission and Fermi Levels Fabricated throughCrystal Phase Engineering[J].Adv Science,2020,7(15):2000930.
[0011] [7]Lei T,Lai M,Kong Q,et al.Electrical and Optical Tunability inAll-Inorganic Halide PerovskiteAlloy Nanowires[J].Nano Lett,2018,18(6):3538-3542.
[0012] [8]Xing D,Lin CC,Ho YL,et al.Self-Healing Lithographic Patterning ofPerovskite Nanocrystals for Large-Area Single-Mode Laser Array[J].Adv FunctMater,2021,31(1):2006283.
[0013] [9] Lei L, Dong Q, Gundogdu K, et al. Metal halide perovskites for laser applications[J]. Adv Funct Mater, 2021, 31(16):2010144. Summary of the invention
[0014] For the existing CsPbCl 3(1–x) Br 3x The first object of the present invention is to provide a large-size CsPbCl 3(1–x) Br 3x Single crystal thin film, aiming to provide a new CsPbCl with large size, grain boundary-free single crystal characteristics, tunability and excellent performance 3(1–x) Br 3x Composite thin film materials.
[0015] The second object of the present invention is to provide the large-sized grain-boundary-free CsPbCl 3(1–x) Br 3x The method for preparing a single crystal thin film is aimed at successfully preparing the large-sized grain boundary-free CsPbCl3(1–x) Br 3x Single crystal thin film.
[0016] The third object of the present invention is to provide the large-sized grain-boundary-free CsPbCl 3(1–x) Br 3x Application of single crystal thin films in tunable lasers and prepared tunable lasers.
[0017] A large-scale grain-boundary-free CsPbCl 3(1–x) Br 3x Single crystal thin film, the plane size (referring to the plane size without grain boundary) is greater than or equal to 0.8cm 2 Grain boundary-free CsPbCl 3(1–x) Br 3x Single crystal thin film, wherein the 0 <x<1;
[0018] The present invention fills the technical gap in the industry and provides for the first time a new CsPbCl with large size, grain boundary-free single crystal structure and ClBr composite phase. 3(1–x) Br 3x Thin film material. Studies have shown that the material has good performance and can be used to prepare high-performance tunable lasers.
[0019] Preferably, the large-sized grain-boundary-free CsPbCl 3(1–x) Br 3x The plane size of the single crystal film is greater than or equal to 0.8 cm 2 , x is 0.2~0.8.
[0020] Preferably, the large-sized grain-boundary-free CsPbCl 3(1–x) Br 3x The thickness of the single crystal film is 1-10 μm.
[0021] The present invention also provides a large-size grain-boundary-free CsPbCl 3(1–x) Br 3x The method for preparing a single crystal thin film comprises mixing a Cs source and a Pb source according to a stoichiometric ratio and heat treating the mixture at a temperature of T1 to obtain CsPbCl 3(1–x) Br 3x Composite material; then the prepared CsPbCl 3(1–x) Br 3x The composite material is heated to T2 under carrier gas and negative pressure and then deposited on a substrate at a temperature of T3 to prepare the large-sized grain-free CsPbCl 3(1–x) Br 3x Single crystal thin film;
[0022] The Cs source includes CsCl and CsBr in a molar ratio of 1-x:x;
[0023] The Pb source comprises PbCl2 and PbBr2 in a molar ratio of 1-x:x;
[0024] When x is less than 0.5, the temperature of T1 is 380-405°C; the temperature of T2 is 600-625°C; the temperature of T3 is 370-385°C;
[0025] When 0.5≤x<1, the temperature of T1 is 340-365°C; the temperature of T2 is 550-575°C; and the temperature of T3 is 335-355°C.
[0026] Different from the conventional preparation of pure phase thin film materials, for CsPbCl 3(1–x) Br 3x For the preparation of single crystal thin films, it needs to face new preparation difficulties, such as the need to overcome CsPbCl 3(1–x) Br 3x The composite phase purity is difficult to control, difficult to form a film, difficult to form a single crystal film, difficult to form a large-size structure without grain boundaries, etc. 3(1–x) Br 3x The technical difficulties faced in the preparation process of single crystal thin films. After in-depth research, the present invention found that the Cs source and the Pb source are pre-heated at the temperature T1, and then the combined control of the temperatures of T2 and T3 under the subsequent negative pressure can achieve synergy, effectively reduce the impurity problem in the preparation of the composite phase, and improve the CsPbCl 3(1–x) Br 3x The phase purity of the composite phase is high, and it is conducive to obtaining CsPbCl with single crystal characteristics and large size without grain boundaries. 3(1–x) Br 3x Single crystal thin film.
[0027] In the present invention, the pre-sintering of the Cs source and the Pb source and the joint control of the temperature of the T1-T3 section are the key to synergistically improving the composite phase and obtaining a large-sized single crystal film.
[0028] In the present invention, heat treatment of stoichiometric Cs source and Pb source in the T1 stage is one of the keys to cooperate with the subsequent process to synergistically improve the phase purity of the composite phase and obtain a large-sized single crystal film.
[0029] Preferably, x=0.1-0.2, and the temperature of T1 is 400-405°C;
[0030] x = 0.3-0.4, the temperature of T1 is 380-385°C;
[0031] x = 0.5-0.6, the temperature of T1 is 360-365°C;
[0032] x=0.7~0.8, the temperature of T1 is 340~345℃.
[0033] In the present invention, under the temperature control of T1, further coordinated with the control of the processing time, it is helpful to further cooperate and facilitate the preparation of the large-size single crystal film. Preferably, the insulation time of the T1 insulation section is 20 to 30 hours; preferably 23 to 25 hours.
[0034] In the present invention, the deposition stage can be carried out in a conventional single-temperature zone or double-temperature zone tube furnace.
[0035] For example, the equipment in the deposition stage of the present invention includes a sealed quartz tube, one end of the quartz tube is provided with an inlet for inputting a carrier gas into the quartz tube chamber, and the other end is provided with an outlet for outputting the gas from the quartz tube chamber; according to the direction of the carrier gas flow, the chamber of the quartz tube is divided into an upstream variable temperature zone, a high-temperature constant temperature zone and a downstream variable temperature zone; the high-temperature constant temperature zone is provided with a heating device, a porcelain boat containing heat treatment materials is placed in the high-temperature constant temperature zone, and a porcelain boat containing a mica substrate is placed downstream.
[0036] The deposition device described in the present invention may be a single temperature zone or multi-temperature zone reaction device, preferably a single temperature zone reaction device.
[0037] In a single temperature zone reaction device, the heating device heats the high temperature constant temperature zone of the quartz tube (usually located in the middle of the quartz tube); the temperature of the area not heated by the heating device changes due to the effect of the carrier gas and the length of the distance from the high temperature constant temperature zone, commonly known as the variable temperature zone, wherein the variable temperature zone near the carrier gas inlet end is the upstream variable temperature zone, and the variable temperature zone located at the carrier gas outlet end is the downstream variable temperature zone. The longer the distance from the high temperature constant temperature zone, the greater the temperature attenuation and the lower the temperature; on the contrary, the shorter the distance to the high temperature constant temperature zone, the closer the temperature is to the temperature of the high temperature constant temperature zone, that is, the temperature value set by the reaction device. For example, during the preparation process, the heat treatment material can be heated by a heating device, and the distance between the porcelain boat of the heat treatment material and the mica substrate porcelain boat can be controlled to volatilize the heat treatment material within a suitable temperature range. The volatilized raw materials are reacted with the assistance of the carrier gas and deposited on the downstream substrate.
[0038] In the present invention, the treatment stages T2 and T3 are carried out under the conditions of carrier gas and negative pressure. The carrier gas is at least one of nitrogen and argon;
[0039] Preferably, x=0.1-0.2, and the temperature of T2 is 620-625°C;
[0040] x = 0.3-0.4, the temperature of T2 is 600-605°C;
[0041] x = 0.5-0.6, the temperature of T2 is 570-575°C;
[0042] x=0.7~0.8, the temperature of T2 is 550~555℃.
[0043] Preferably, the flow rate of the carrier gas is 70 to 120 sccm;
[0044] Preferably, in T3, x=0.1-0.2, and the temperature of T3 is 380-385°C;
[0045] x = 0.3-0.4, the temperature of T3 is 370-375°C;
[0046] x = 0.5-0.6, the temperature of T3 is 345-355°C;
[0047] x=0.7~0.8, the temperature of T3 is 335~340℃.
[0048] Preferably, the distance between the substrate and the T2 temperature zone is 10 to 15 cm.
[0049] In the present invention, the substrate may be a conventional substrate in the industry, such as mica;
[0050] Preferably, the negative pressure is less than or equal to 200 Mbar, preferably 10 to 150 Mbar.
[0051] Preferably, the deposition time is 30 to 60 min, preferably 30 to 40 min.
[0052] The present invention also includes the large-size grain-boundary-free CsPbCl 3(1–x) Br 3x The application of single crystal thin films is to prepare tunable lasers.
[0053] The present invention can be based on existing means to convert the large-size grain-boundary-free CsPbCl 3(1–x) Br 3x Single crystal thin films are prepared into the required tunable lasers.
[0054] For example, using large-scale grain boundary-free CsPbCl 3(1–x) Br 3x The steps of preparing a tunable laser from a single crystal thin film include:
[0055] S1: Focus the pump light and irradiate it on CsPbCl 3(1–x) Br 3x A pump spot is formed on the surface of the single crystal film;
[0056] S2: Control the modulated light intensity to achieve continuous adjustment of the output wavelength.
[0057] S3: Replace different CsPbCl3(1–x) Br 3x Single crystal thin film, modulated light intensity, achieving adjustable amplified spontaneous emission from blue to green light at room temperature.
[0058] Preferably, in S1, the pump light spot is a linear light spot, and the linear light spot intersects the edge of the substrate perpendicularly, and the strip light spot excites the CsPbCl 3(1–x) Br 3x The amplified spontaneous emission or lasing generated by the single-crystal thin film is collected laterally.
[0059] Preferably, the pumping experiment is performed at room temperature.
[0060] Preferably, the pump laser is a 400 nm laser with a repetition frequency of 1 kHz and a pulse width of about 100 fs.
[0061] Preferably, in S1, the length of the strip light spot is 650 μm and the width is 350 μm.
[0062] The present invention also provides a method for utilizing the large-size grain-boundary-free CsPbCl 3(1–x) Br 3x Tunable laser made from single crystal thin film
[0063] Beneficial Effects
[0064] The present invention provides a new large-size grain boundary-free CsPbCl 3(1–x) Br 3x The single crystal thin film, thanks to the combination of the physical phase, single crystal and large size characteristics, can show excellent tunability and optical gain performance.
[0065] The present invention also provides a method for solving the problem of difficulty in forming large-size, single crystal and CsPbCl 3(1–x) Br 3x The preparation method of the phase film innovatively pre-heats the chemically dosed CsPb raw material in the T1 stage, and then cooperates with the combined control of the temperature of the T2 and T3 stages to achieve unexpected synergy, effectively improve the phase purity, and obtain large-sized CsPbCl with no grain boundaries and single crystal characteristics. 3(1–x) Br 3x film. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 CsPbCl prepared in Example 1 2.4 Br 0.6 EDS spectrum of powder.
[0067] Figure 2 Preparation of CsPbCl for Example 1 2.4 Br0.6 Schematic diagram of the vapor deposition apparatus for single crystal thin films.
[0068] Figure 3 Example 1 CsPbCl 2.4 Br 0.6 Thin film EDS spectrum Figure 3 shown.
[0069] Figure 4 Example 1 CsPbCl 2.4 Br 0.6 Camera image of a single-crystal thin film.
[0070] Figure 5 Example 1 CsPbCl 2.4 Br 0.6 Optical images of single crystal thin films
[0071] Figure 6 a is CsPbCl in Example 1 2.4 Br 0.6 SEM images of the film. Figure 6 b is CsPbCl 2.4 Br 0.6 EBSPs patterns at different locations on the film.
[0072] Figure 7 Example 2 CsPbCl 1.8 Br 1.2 Thin film EDS spectrum.
[0073] Figure 8 a is Example 2CsPbCl 1.8 Br 1.2 SEM images of the film. Figure 8 b is CsPbCl 2.4 Br 0.6 EBSPs patterns at different locations on the film.
[0074] Fig. 9 Example 3 CsPbCl 1.2 Br 1.8 Thin film EDS spectrum.
[0075] Fig.10 a is Example 3CsPbCl 1.2 Br 1.8 SEM images of the film. Fig.10 b is CsPbCl 1.2 Br 1.8 EBSPs patterns at different locations on the film.
[0076] Fig.11 Example 4 CsPbCl 0.6 Br2.4 Thin film EDS spectrum.
[0077] Fig.12 a is Example 4CsPbCl 0.6 Br 2.4 SEM images of the film. Fig.12 b is CsPbCl 0.6 Br 2.4 EBSPs patterns at different locations on the film.
[0078] Fig.13 CsPbCl synthesized in Comparative Example 1 1.8 Br 1.2 Optical image of the nanosheet.
[0079] Fig.14 CsPbCl synthesized in Comparative Example 2 1.8 Br 1.2 Optical image of nanorods.
[0080] Fig.15 CsPbCl synthesized in Comparative Example 3 1.8 Br 1.2 Optical image of nanosheets.
[0081] Fig.16 The incomplete CsPbCl synthesized in Comparative Example 4 1.8 Br 1.2 Thin film optics image.
[0082] Fig.17 CsPbCl with dendrite morphology of Comparative Example 5 1.8 Br 1.2 Material.
[0083] Fig.18 This is the EDS energy spectrum of the CsPbCl3 film synthesized in Comparative Example 6.
[0084] Fig.19 a is the SEM image of the CsPbCl3 film synthesized in Comparative Example 6, Fig.19 b: EBSPs patterns at different positions of CsPbCl3 film.
[0085] Fig. 20 Example 5 CsPbCl 1.8 Br 1.2 Gain curve measured for the film (prepared in Example 2).
[0086] Fig.21 This is the gain curve measured for the CsPbCl3 thin film (prepared in Comparative Example 6) involved in Comparative Example 7. Specific implementation methods
[0087] In order to facilitate the understanding of the present invention, the present invention is described in more detail below in conjunction with the accompanying drawings and specific embodiments. Preferred embodiments of the present invention are provided in the accompanying drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0088] Example 1
[0089] Step (1): CsPbCl 2.4 Br 0.6 Preparation of powder:
[0090] First, CsCl and CsBr powders were mixed in a molar ratio of 4:1, and then PbCl2 and PbBr2 powders were added in a molar ratio of 4:1, where the molar ratio of Cs / Pb was 1:1. After sufficient grinding, the porcelain boat containing the mixed powders was placed in the center of the constant temperature zone of the tube furnace. A solid phase reaction occurred under the action of protective gas (Ar). The reaction temperature T1 was 400°C and the reaction time was 24 hours. CsPbCl was obtained. 2.4 Br 0.6 Precursor powder. CsPbCl reacts evenly 2.4 Br 0.6 The EDS spectrum of the precursor powder is as follows: Figure 1 As shown. The atomic ratio of elements Cs, Pb, Cl, and Br is 18.1:19.6:50.9:11.4. This indicates that CsPbCl was successfully prepared. 2.4 Br 0.6 Perovskite powder precursor.
[0091] Step (2): CsPbCl 2.4 Br 0.6 Preparation of single crystal thin films:
[0092] Preparation of CsPbCl 2.4 Br 0.6 Schematic diagram of the vapor deposition apparatus for single crystal thin films is shown in Figure 2 , including a quartz tube 1, the left side of which is a high temperature constant temperature zone, which is loaded with CsPbCl 2.4 Br 0.6 The porcelain boat 2 of the precursor powder is placed in the center of the tube furnace, and the base mica sheet 4 is placed about 12 cm away from the high temperature constant temperature zone. The growth time is 30 min. The device is also provided with a pressure-controllable pump to control the pressure in a low pressure state (100 mbar).
[0093] Both ends of the quartz tube 1 are provided with air holes, wherein the air hole at the left end of the quartz tube 1 is an air inlet hole, and the air hole at the right end of the quartz tube 1 is an air outlet hole.
[0094] The carrier gas is protective gas argon, wherein the flow rate of the protective gas is 100 sccm; the pressure of the control system is 100 mbar, the temperature T2 of the pre-prepared precursor heated and volatilized is 620°C; the substrate is mica, the deposition temperature T3 of the substrate is 380°C, and it grows on the surface of the substrate for 30 minutes to form a large-sized single crystal film without grain boundaries.
[0095] Figure 2 3 in the figure is the product of chemical vapor deposition, CsPbCl 2.4 Br 0.6 Single crystal thin film. CsPbCl 2.4 Br 0.6 Thin film EDS spectrum Figure 3 As shown in the figure, the atomic ratio of elements Cs, Pb, Cl:Br is 18.0:19.1:51.1:11.8. This indicates that CsPbCl was successfully prepared. 2.4 Br 0.6 film. Figure 4 CsPbCl 2.4 Br 0.6 Camera photo of a single-crystal thin film. Figure 5 CsPbCl 2.4 Br 0.6 Microscope photo of a single crystal thin film. Figure 6 a is CsPbCl 2.4 Br 0.6 SEM images of the film. Figure 6 b is CsPbCl 2.4 Br 0.6 The EBSPs patterns at different positions of the film show that the film orientations at different positions are consistent, confirming that the prepared film is a perovskite single crystal film.
[0096] Example 2
[0097] Step (1): CsPbCl 1.8 Br 1.2 Preparation of powder:
[0098] Compared with Example 1, the difference is that the molar ratio of CsCl and CsBr powder is 3:2, and the reaction temperature T1 is 380°C;
[0099] Step (2): CsPbCl 1.8 Br 1.2 Preparation of single crystal thin films
[0100] Compared with Example 1, the difference is that the temperature T2 of the pre-prepared precursor for heating and volatilization is 600°C and T3 is 370°C. 1.8 Br 1.2 Thin film EDS spectrum Figure 7As shown in the figure, the atomic ratio of elements Cs, Pb, Cl, and Br is 19.7:20.3:39.2:20.8. This indicates that CsPbCl 1.8 Br 1.2 film. Figure 8 a is CsPbCl 1.8 Br 1.2 SEM images of the film. Figure 8 b is CsPbCl 1.8 Br 1.2 The EBSPs patterns at different positions of the film show that the film orientations at different positions are consistent, confirming that the prepared film is a single crystal film.
[0101] Example 3
[0102] Step (1): CsPbCl 1.2 Br 1.8 Preparation of powder:
[0103] Compared with Example 1, the difference is that the molar ratio of CsCl and CsBr powder is 2:3, and the reaction temperature T1 is 360°C;
[0104] Step (2): CsPbCl 1.2 Br 1.8 Preparation of single crystal thin films
[0105] Compared with Example 1, the difference is that the temperature T2 of the pre-prepared precursor for heating and volatilization is 570°C and T3 is 349°C. 1.2 Br 1.8 Thin film EDS spectrum Fig. 9 As shown in the figure, the atomic ratio of elements Cs, Pb, Cl, and Br is 18.1:19.6:25.6:36.7. This indicates that CsPbCl 1.2 Br 1.8 film. Fig.10 a is CsPbCl 1.2 Br 1.8 SEM images of the film. Fig.10 b is CsPbCl 1.2 Br 1.8 The EBSPs patterns at different positions of the film show that the film orientations at different positions are consistent, confirming that the prepared film is a single crystal film.
[0106] Example 4
[0107] Step (1): CsPbCl 0.6 Br 2.4 Preparation of powder:
[0108] Compared with Example 1, the difference is that the molar ratio of CsCl and CsBr powder is 1:4, and the reaction temperature T1 is 340°C;
[0109] Step (2): CsPbCl 0.6 Br 2.4 Preparation of single crystal thin films
[0110] Compared with Example 1, the difference is that the temperature T2 of the pre-prepared precursor for heating and volatilization is 550°C and T3 is 336°C. 0.6 Br 2.4 Thin film EDS spectrum Fig.11 As shown in the figure, the atomic ratio of elements Cs, Pb, Cl, and Br is 18.9:19.4:13.1:48.6. This indicates that CsPbCl 0.6 Br 2.4 film. Fig.12 a is CsPbCl 0.6 Br 2.4 SEM images of the film. Fig.12 b is CsPbCl 0.6 Br 2.4 The EBSPs patterns at different positions of the film show that the film orientations at different positions are consistent, confirming that the prepared film is a single crystal film.
[0111] Comparative Example 1
[0112] Compared with Example 2, the only difference is that the heat preservation treatment of section T1 of step (1) is not performed, but the raw material powder is used as raw material and step (2) is directly performed, and the parameters and conditions of step 2 are the same as those of Example 2.
[0113] The obtained product is shown in Fig.13 , Fig.13 It can be seen that CsPbCl was obtained 1.8 Br 1.2 Optical image of nanosheets. CsPbCl cannot be prepared. 1.8 Br 1.2 Single crystal thin film.
[0114] Comparative Example 2
[0115] Compared with Example 2, the only difference is that the treatment process of step (2) is changed, for example, the temperature of section T2 is 570°C, T3 is 349°C, the growth time is 30 minutes, and the pressure reading is 100 mbar. Fig.14 For the preparation of CsPbCl 1.8 Br 1.2 Optical image of the sample. Nanorods were obtained but no thin film was obtained.
[0116] Comparative Example 3
[0117] Compared with Example 2, the only difference is that the temperature of section T2 in step (2) is changed to 580°C and T3 is changed to 354°C. Other operations and parameters are the same as those in Example 2. Fig.15 For the preparation of CsPbCl 1.8 Br 1.2 Optical image of the sample. Nanosheets were prepared but no thin film was obtained.
[0118] Comparative Example 4
[0119] Compared with Example 2, the only difference is that the temperature of section T2 in step (2) is changed to 590°C and T3 is changed to 363°C. Other operations and parameters are the same as those in Example 2. Fig.16 For the preparation of CsPbCl 1.8 Br 1.2 Optical image of the sample shows that the prepared film has gaps and it is impossible to obtain a large-area film.
[0120] Comparative Example 5
[0121] Compared with Example 2, the only difference is that the pressure in the deposition stage is 1 atm (normal pressure), and other operations and parameters are the same as Example 2. Fig.17 For the preparation of CsPbCl 1.8 Br 1.2 Optical image of the sample, showing a leaf-like morphology.
[0122] Comparative Example 6
[0123] Comparative example of CsPbCl3;
[0124] Step (1): Preparation of CsPbCl3 powder:
[0125] Compared with Example 1, the difference is that the molar ratio of CsCl and PbCl2 powder is 1:1, and the reaction temperature T1 is 420°C;
[0126] Step (2): Preparation of CsPbCl3 single crystal thin film
[0127] Compared with Example 1, the difference is that the temperature T2 of the pre-prepared precursor for heating and volatilization is 650°C and T3 is 405°C. 1.8 Br 1.2 Thin film EDS spectrum Fig.18 As shown, the atomic ratio of the elements Cs, Pb, and Cl is 18.9:19.0:62.1, which is about 1:1:3. This indicates that the CsPbCl3 film was successfully prepared. Fig.19 a is the SEM image of CsPbCl3 film. Fig.19b is the EBSPs pattern of different positions of the CsPbCl3 film, indicating that the film orientations at different positions are consistent, confirming that the prepared film is a single crystal film.
[0128] Example 5
[0129] Control the modulated light intensity between 5-80μj·cm 2 Range, CsPbCl measured at room temperature 1.8 Br 1.2 The blue amplified spontaneous emission (ASE) threshold of the single crystal film (prepared in Example 2) is P th =35.2uj / cm 2 , the output wavelength is 452nm. The pump laser uses 400nm laser, the repetition frequency is 1kHz, and the pulse width is about 100fs.
[0130] CsPbCl 1.8 Br 1.2 The test method of single crystal thin film optical gain is to focus the pump light into a strip spot through a cylindrical lens and irradiate it on CsPbCl 1.8 Br 1.2 A pump spot is formed on the surface of the single crystal film. The spectrum is obtained by changing the spot width from 0-0.1cm at 2 times, 5 times, 10 times, 20 times, and 25 times the threshold light intensity. Then, according to the formula I0(L)=I s A / g[exp(gL)-1] is fitted to obtain the gain coefficient. Where g is the gain coefficient, L is the spot width, I0(L), I s is the PL intensity and radiance collected per unit volume, and A is the excitation area. When the light intensity increases from 2 to 20 times the threshold, the optical gain coefficient gradually increases. When the light intensity increases to 25 times the threshold, the optical gain coefficient begins to decrease. Fig. 20 The figure shows the optical gain curve of variable spot width obtained at 20 times the threshold light intensity. The optical gain coefficient after fitting is g = 860.9 cm -1 .
[0131] Comparative Example 7
[0132] Compared with Example 5, the difference is that the test material is CsPbCl3 single crystal film (prepared in Comparative Example 6), and blue amplified spontaneous emission (ASE) is also achieved under the same conditions, with a threshold of P th =39.6uj / cm 2 , the output wavelength is 432nm. When the light intensity increases from 2 to 20 times the threshold, the optical gain coefficient gradually increases, and when the light intensity increases to 25 times the threshold, the optical gain coefficient begins to decrease. Fig.21 The figure shows the optical gain curve of variable spot width obtained at 20 times the threshold light intensity. The optical gain coefficient after fitting is g = 616.43 cm-1 。
Claims
1. A large-scale grain-boundary-free CsPbCl 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The Cs source and the Pb source are mixed in a stoichiometric ratio and then heat treated at a temperature of T1 to obtain CsPbCl 3(1–x) Br 3x Composite material; then the prepared CsPbCl 3(1–x) Br 3x The composite material is heated to T2 under carrier gas and negative pressure and then deposited on a substrate at a temperature of T3 to prepare the large-sized grain-free CsPbCl 3(1–x) Br 3x Single crystal thin film; The Cs source comprises CsCl and CsBr in a molar ratio of 1-x:x; The Pb source comprises PbCl2 and PbBr2 in a molar ratio of 1-x:x; When x is less than 0.5, the temperature of T1 is 380-405°C; the temperature of T2 is 600-625°C; the temperature of T3 is 370-385°C; When 0.5≤x<1, the temperature of T1 is 340~365°C; the temperature of T2 is 550~575°C; and the temperature of T3 is 335~355°C.
2. The large-sized grain boundary-free CsPbCl according to claim 1 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: x = 0.1~0.2, the temperature of T1 is 400~405℃; x = 0.3~0.4, the temperature of T1 is 380~385℃; x = 0.5~0.6, the temperature of T1 is 360~365℃; x=0.7~0.8, the temperature of T1 is 340~345℃.
3. The large-sized grain boundary-free CsPbCl according to claim 2 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The insulation time of T1 insulation section is 20~30h.
4. The large-sized grain boundary-free CsPbCl according to claim 3 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The insulation time of T1 insulation section is 23~25h.
5. The large-sized grain boundary-free CsPbCl according to claim 1 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: x = 0.1~0.2, the temperature of T2 is 620~625℃; x = 0.3~0.4, the temperature of T2 is 600~605℃; x = 0.5~0.6, the temperature of T2 is 570~575℃; x=0.7~0.8, the temperature of T2 is 550~555℃.
6. The large-scale grain boundary-free CsPbCl according to claim 5 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: In T3, x = 0.1~0.2, and the temperature of T3 is 380~385℃; x = 0.3~0.4, the temperature of T3 is 370~375℃; x = 0.5~0.6, the temperature of T3 is 345~355℃; x=0.7~0.8, the temperature of T3 is 335~340℃.
7. The large-scale grain-boundary-free CsPbCl according to claim 5 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The distance between the substrate and the T2 temperature zone is 10-15 cm.
8. The large-scale grain boundary-free CsPbCl according to claim 1 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The negative pressure is less than or equal to 200 mbar.
9. The large-scale grain boundary-free CsPbCl according to claim 1 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The deposition time is 30~60min.
10. The large-scale grain boundary-free CsPbCl according to claim 1 3(1–x) Br 3x A method for preparing a single crystal thin film, characterized in that: The substrate is mica.
11. A large-sized grain-boundary-free CsPbCl prepared by the preparation method according to any one of claims 1 to 10 3(1–x) Br 3x A single crystal thin film, characterized in that The plane size is greater than or equal to 0.8 cm 2 Grain boundary-free CsPbCl 3(1–x) Br 3x Single crystal thin film, where 0 <x<1。 12. The large-scale grain boundary-free CsPbCl according to claim 11 3(1–x) Br 3x A single crystal thin film, characterized in that The large-scale grain-boundary-free CsPbCl 3(1–x) Br 3x The planar size of the single crystal film is greater than or equal to 1 cm 2 , x is 0.2~0.
8.
13. The large-scale grain boundary-free CsPbCl according to claim 11 3(1–x) Br 3x A single crystal thin film, characterized in that The large-scale grain-boundary-free CsPbCl 3(1–x) Br 3x The thickness of the single crystal film is 1-10 μm.
14. A large-sized grain-boundary-free CsPbCl prepared by the preparation method according to any one of claims 1 to 10 3(1–x) Br 3x Application of single crystal thin film, characterized in that, It is used to prepare a tunable laser.
15. A tunable laser made by the application of claim 14.
Citation Information
Patent Citations
All-inorganic halogen perovskite monocrystal X-ray detector and preparation method thereof
CN110611004A
Preparation method of non-solvent-based all-inorganic Pb-based perovskite film
CN111925128A